Ensuring Access to Medicines in Frame of the Right to Share in Scientific Advancement and its Benefits - Aslan Khuseinovich Abashidze; Vladislav Malichenko (LeXonomica, 2019)
A significant role in providing access to medicines is rightfully played by legal norms regulating intellectual property protection. The pharmaceutical sector stands out among other industries in terms of implementation of various mechanisms of intellectual property rights protection, which guarantee the possibility to recover economic losses due to tremendous investments in R&D. However, intellectual property protection mechanisms trigger the rise of medication costs, which significantly influence state expenditures and limit patient’s access to treatment. At the time of scientific achievements access to medicines is directly linked with the right “to enjoy the benefits of scientific progress and its applications”. It means that initiatives implemented by international organizations and national healthcare policies should contain balanced approach between the interests of the society and pharmaceutical producers in order to protect public and private interests.